2017
DOI: 10.1111/avsc.12321
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of floristic change in grassland: landscape, land use legacy and seasonal conditions overshadow restoration actions

Abstract: Questions How does ground‐layer plant composition respond to the imposition of woodland habitat restoration treatments following the removal of long‐term pastoral management? Do different vegetation types have different trajectories of change? Location A long‐term ecological research site comprising temperate eucalypt grassy woodland and forest in south‐eastern Australia, converted from pastoral use to conservation management. This has involved the implementation of habitat restoration treatments in addition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…The finding that exclusion of grazing did not produce changes in lowland grassland composition finds much support in the literature on grazing exclusion in southeastern Australian temperate grasslands; Zimmer et al (2010), Lewis et al (2008), Foreman (1996), Schultz et al (2014), McIntyre et al (2017) and Souter and Milne (2009) all found that species richness did not change significantly with grazing exclusion. By contrast, studies in more productive grasslands have shown that grazing exclusion will quickly (2–5 years) disadvantage inter‐tussock flora (e.g.…”
Section: Discussionmentioning
confidence: 68%
“…The finding that exclusion of grazing did not produce changes in lowland grassland composition finds much support in the literature on grazing exclusion in southeastern Australian temperate grasslands; Zimmer et al (2010), Lewis et al (2008), Foreman (1996), Schultz et al (2014), McIntyre et al (2017) and Souter and Milne (2009) all found that species richness did not change significantly with grazing exclusion. By contrast, studies in more productive grasslands have shown that grazing exclusion will quickly (2–5 years) disadvantage inter‐tussock flora (e.g.…”
Section: Discussionmentioning
confidence: 68%
“…Efforts in Canberra Nature Park to reverse the effects of historic heavy livestock grazing, and ongoing kangaroo grazing, show only modest recovery of grazing‐sensitive species, and document a perennial flora that is resistant to change, even after four years of favourable rainfall and reduced grazing pressure (McIntyre et al. 2010, 2017). It should be noted that localised species losses would likely be permanent within the fragmented grassy ecosystems of Canberra Nature Park; therefore, a consistent landscape scale approach to the management of kangaroo populations is essential for the conservation of endangered ecological communities in this context.…”
Section: Kangaroo Management In the Australian Capital Territory (Act)mentioning
confidence: 99%
“…Such long‐term directional trends can be due to land‐use changes, climate change or to succession after disturbance, among other processes, and are particularly frequent in grasslands (Lepš, Götzenberger, et al, 2019; Stevens et al, 2011; Valencia, de Bello, Lepš, et al, 2020). Land‐use changes such as fertilization can lead to the presence of relatively long‐term trends due to the legacy effects over time of past fertilization treatments and can modulate the impact of climate change (McIntyre et al, 2017). Long‐term trends present a methodological and conceptual issue when studying synchrony and community stability (Lepš, Götzenberger, et al, 2019; Valencia, de Bello, Lepš, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%